2008
DOI: 10.1111/j.1600-0846.2008.00306.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of correlation between minimal erythema dose and skin phototype in a colombian scholar population

Abstract: The Fitzpatrick's classification was not useful in Hispanic populations such as ours. Therefore, a new skin-phototype classification system is required. In our population the constitutional color was a good predictor of the MED but it did not correlate with skin phototype. The self-assessed questionnaire method was not useful to determine skin cancer risk in our population. The majority of this population has light skin phototypes and is highly exposed to solar UV radiation without proper protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 28 publications
1
9
0
2
Order By: Relevance
“…Limited evidence for differences in tanning response between Indigenous American and European individuals comes from studies of phototype in Colombia (Sanclemente et al 2008). This research found a small association between MED and phototype and, as in East Asian populations, an overall difference in photosensitivity between Europeans and admixed Colombians.…”
Section: Population-level Variability In Sensitivity and Persistence mentioning
confidence: 68%
“…Limited evidence for differences in tanning response between Indigenous American and European individuals comes from studies of phototype in Colombia (Sanclemente et al 2008). This research found a small association between MED and phototype and, as in East Asian populations, an overall difference in photosensitivity between Europeans and admixed Colombians.…”
Section: Population-level Variability In Sensitivity and Persistence mentioning
confidence: 68%
“…A number of studies have suggested a strong correlation between pigmentary phenotypes and FSPT in Caucasians 1315 , but studies in Korea, Thailand and Colombia 1619 did not find such correlation. These data suggest that pigmentary phenotypes may be predictive of FSPT in Caucasians, but not in non-Caucasian minorities, rendering PSPT a less effective method of assessing skin cancer risk in an ethnically diverse population like the U.S. Physicians frequently overestimate sunburn risk for Caucasians based on patient appearance and underestimate sunburn risk for racial minorities 20 .…”
Section: Discussionmentioning
confidence: 94%
“…There has been a tendency to group people of similar ethnic group into a single category of SPT, which introduces potential bias into the subjective assessment of SPT by investigators [25][26][27] . The limitations of Fitzpatrick SPT, especially in people with darker skin [28,29] , include recall bias, subjective bias by clinicians and subjects, lack of cultural sensitivity of the questions, and adherence to sun protection recommendations, resulting in children not having experienced prior sunburns. Although skin pigmentation is not the only factor that plays a role in protection against sunburn [11] , it remains an important risk factor for skin cancer development.…”
Section: Resultsmentioning
confidence: 99%